1997
DOI: 10.1084/jem.185.10.1721
|View full text |Cite
|
Sign up to set email alerts
|

When Do Microbes Stimulate Rheumatoid Factor?

Abstract: A nti-␥ -globulins or rheumatoid factors (RF) were first described in the early 1940s. They are present in Ͼ 70% of patients with rheumatoid arthritis (RA) and high titers are associated with severe disease, but they also appear in a large number of other diseases including viral, bacterial, and parasitic infections (1). In spite of their wide spread occurrence, it is still a puzzle how or why RF are generated.RF come in two varieties. Low affinity RF (K d of ‫ف‬ 10 Ϫ 5 M) are IgM natural antibodies with speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 23 publications
0
28
0
2
Order By: Relevance
“…One is due to chronic exposure of B cells to repetitive epitopes on the viral surface that maintains polyclonal B-cell activation through a T-cell-independent mechanism. The other occurs when the virus epitopes are presented in immune complexes and therefore induce a T-celldependent and antigen-specific RF production (26). In our model, we suppose that this antigen-specific event is missing, probably due to the incapacity of influenza virus to directly activate B cells.…”
Section: Discussionmentioning
confidence: 98%
“…One is due to chronic exposure of B cells to repetitive epitopes on the viral surface that maintains polyclonal B-cell activation through a T-cell-independent mechanism. The other occurs when the virus epitopes are presented in immune complexes and therefore induce a T-celldependent and antigen-specific RF production (26). In our model, we suppose that this antigen-specific event is missing, probably due to the incapacity of influenza virus to directly activate B cells.…”
Section: Discussionmentioning
confidence: 98%
“…Previous work showed that acute polyarthritis was observed in association with EBV infection (11), increased Ab titers were found in RA (12)(13)(14), molecular mimicry was entertained (15,16), and CD8 cell clones specific for lytic and latent EBV gene products were clonally expanded in inflamed synovia (17)(18)(19)(20). Staining with MHC class I peptide tetramers showed that EBV-specific CD8 T cells were enriched in RA synovia compared with blood from the same subject (21,22).…”
Section: A Mouse Herpesvirus Induces Relapse Of Experimentalmentioning
confidence: 99%
“…While high titers of rheumatoid factor (RF) are associated with severe rheumatoid arthritis, they also appear in a number of other diseases including viral, bacterial and parasitic infections. 23 Maturation of RF can be initiated by chronic infections. 24 For example, patients with subacute bacterial endocarditis, which is frequently tied to the presence of Streptococcus, also often present with high levels of RF.…”
Section: Communities Of Microbes Drive Autoimmune Diseasementioning
confidence: 99%